Glycine-gated chloride channels depress synaptic transmission in rat hippocampus - Weifeng Song (2018)
An inhibitory role for strychnine-sensitive glycine-gated chloride channels (GlyRs) in mature hippocampus is beginning to be appreciated. We have reported previously that CA1 pyramidal cells and GABAergic interneurons recorded in 3- to 4-wk-old rat hippocampal slices express functional GlyRs, dispelling previous misconceptions that GlyR expression ceases in early development. However, the effect of GlyR activation on cell excitability and synaptic circuits in hippocampus has not been fully explored. Using whole cell current-clamp recordings, we show that activation of strychnine-sensitive GlyRs through exogenous glycine application causes a significant decrease in input resistance and prevents somatically generated action potentials in both CA1 pyramidal cells and interneurons. Furthermore, GlyR activation depresses the synaptic network by reducing suprathreshold excitatory postsynaptic potentials (EPSPs) to subthreshold events in both cell types. Blockade of postsynaptic GlyRs with the chloride channel blocker 4, 4′- diisothiocyanatostilbene-2-2′-disulfonic acid (DIDS) or altering the chloride ion driving force in recorded cells attenuates the synaptic depression, strongly indicating that a postsynaptic mechanism is responsible. Increasing the local glycine concentration by blocking reuptake causes a strychnine-sensitive synaptic depression in interneuron recordings, suggesting that alterations in extracellular glycine will impact excitability in hippocampal circuits. Finally, using immunohistochemical methods, we show that glycine and the glycine transporter GlyT2 are co-localized selectively in GABAergic interneurons, indicating that interneurons contain both inhibitory neurotransmitters. Thus we report a novel mechanism whereby activation of postsynaptic GlyRs can function to depress activity in the synaptic network in hippocampus. Moreover, the co-localization of glycine and GABA in hippocampal interneurons, similar to spinal cord, brain stem, and cerebellum, suggests that this property is likely to be a general characteristic of inhibitory interneurons throughout the CNS. Copyright © 2006 The American Physiological Society.